2 - Negotiating Marriage on the Eve of Human Rights - Kirsten Besendahl, (African Sociological Review, 2004)
This paper examines the case of women’s rights in marriage. It adopts a pluralist perspective on law and rights that highlights the complex legal framework within which women negotiate marriage. Based on research carried out in two Malawian cities in 2000-2001, it focuses on the interplay between different types of laws and norms related to marriage and discusses the opportunities and limitations women experience when negotiating polygynous marriages. One important aspect of the plural legal framework in contemporary Africa is the concept of human rights, which has accompanied the democratisation proces. The paper draws attention women’s rights on the legal framework in Malawi.